A sustainable production of biocement via microbially induced calcium carbonate precipitation. (August 2022) - Liang, Haixia; Liu, Yunqi; Tian, Baohua; Li, Zhu; Ou, Hengan
Graphical abstract: Image 1 Highlights: Circulating fluidized bed combustion fly ash provided calcium source for microbially induced calcium carbonate precipitation. Circulating fluidized bed combustion fly ash underwent hydrate reaction. The hydration product C-S-H promoted CaCO3 precipitation and contributed to strength. The approach has the potential of application in geotechnical engineering field.